Perceptions of Literacy in the Teaching and Learning Process with Student Achievement Motivation at Senior High School of Deli Murni Bandar Baru - Purba, Saut; Kefi, Yohanes; Ramadhani, Taufiq (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Senior High School of Deli Murni Bandar Baru is located in the Bandar Baru area, Deli Serdang District, North Sumatra, where from a number of students, few have literacy skills in understanding, and mastering subjects and learning materials comprehensively. The literacy ability of some students that is difficult to apply is the ability to explain the material in class, where the weak ability of some students to increase literacy understanding of learning material will have an impact on decreasing student achievement so that existing motivation will decrease and make the achievement of Deli Murni Bandar Baru High School students hampered. The purpose of this study is to determine and analyze the influence of literacy on the teaching-learning process on the achievement motivation of Senior High School of Deli Murni Bandar Baru students. The research method used is a quantitative descriptive research method, where the results of the study can be described that the literacy of the teaching and learning process at Deli Murni Private High School has a significant effect on the motivation of student achievement at Deli Murni private high school school.